Efektivitas Perendaman Serat Aren dan Endosperm Kelapa Terhadap Pertumbuhan dan Hasil Tomat Pada Hidroponik Substrat - Sulandjari, Sulandjari; Kusniyawati, Yuni (Agrosains : Jurnal Penelitian Agronomi, 2017)
This study was conducted to determine the effect of soaking period of arenga  fibers and the addition of coconut endosperm to growth and yield of tomatoe. The observations were analyzed by using the 5% F test and if significant continued by the 5% DMRT. The experiment was conducted using a completely randomized factorial design with two factors, factors substrate consists of 5 levels, fiber arenga  without soaking (S0), fiber soaking for 1 month (S1),  fiber soaking for 2 months (S2), fiber soaking for 3 months(S3),  and substrate husk as control. The second factor is a nutrient with two levels ie. AB mix nutrient (N1), AB mix nutrient plus 50% coconut endosperm (N2). The results showed that treatment of arenga fiber substrate by immersion of one month, 2 month, and 3 month not significantly influenced on all growth variable and  yield of tomato. Treatment spraying coconut endosperm with a concentration of 50% could be low variable root length, root volume and fresh weight of the plant. There was no interaction between the two factors of all the observed variables.